Determinan Minat Mahasiswa Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi Menabung Pada Bank Syariah XYZ - Habriyanto Habriyanto; Bambang Kurniawan (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2021)
This study is related to the factors that influence the interest of sharia faculty students to save their money at Bank Syariah Mandiri Jambi branch. The findings of this study are the factors that influence public interest among students at the Jambi branch of the Mandiri syariah bank, which are almost 50% better known that the factors of facilities, services, education, confidence and economic benefits on the interest in saving among students at the Jambi branch of the Syariah Mandiri bank. Based on the test using partial regression, the facility and service factors did not affect the interest in saving. While the factors of education, belief and economic profit motive influence. If the test is carried out simultaneously between the variables of facilities, services, education, confidence and economic benefits, this variable affects the interest in saving among students of the UIN STS Jambi at the Jambi branch of the Syariah Mandiri bank with the amount of influence is 67.1% and the rest is determined by other factors not related to the research.